2019
DOI: 10.1101/727842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using high-definition transcranial direct current stimulation to investigate the role of the dorsolateral prefrontal cortex in explicit sequence learning

Abstract: Though we have a general understanding of the brain areas involved in motor sequence learning, there is more to discover about the neural mechanisms behind which a new skill is learned. Initial skill acquisition may be subserved, in part, by interactions between the cerebellum (CBLM) and prefrontal cortex (PFC) through a cerebello-thalamo-prefrontal network. We investigated the consequence of stimulating the PFC using high-definition transcranial direct current stimulation (HD-tDCS) before administering an exp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…While this focal montage can induce greater changes in cortical excitability and facilitate movement response times when compared to the conventional montage ( Masina et al, 2021 ; Kuo et al, 2013 ), it remains unclear whether a more-targeted approach is beneficial for motor learning. Indeed, utilizing the 4 × 1 ring configuration in the context of motor learning has led to some mixed results ( Doppelmayr et al, 2016 ; Cole et al, 2018 ; Ballard et al, 2021 ), which likely depend on the target-site ( Lefebvre et al, 2019 ) and stimulation intensity ( Lerner et al, 2021 ). Of these studies, only Cole and colleagues have compared the effects of focal and conventional tDCS on fine motor skill performance in children and found that both montages similarly improved manual dexterity compared to sham.…”
mentioning
confidence: 99%
“…While this focal montage can induce greater changes in cortical excitability and facilitate movement response times when compared to the conventional montage ( Masina et al, 2021 ; Kuo et al, 2013 ), it remains unclear whether a more-targeted approach is beneficial for motor learning. Indeed, utilizing the 4 × 1 ring configuration in the context of motor learning has led to some mixed results ( Doppelmayr et al, 2016 ; Cole et al, 2018 ; Ballard et al, 2021 ), which likely depend on the target-site ( Lefebvre et al, 2019 ) and stimulation intensity ( Lerner et al, 2021 ). Of these studies, only Cole and colleagues have compared the effects of focal and conventional tDCS on fine motor skill performance in children and found that both montages similarly improved manual dexterity compared to sham.…”
mentioning
confidence: 99%
“…Although this has been the first time that both the DLPFC and the PPC have been targeted with the use of bifocal stimulation during a sequence learning task, studies have targeted the two areas separately. Stimulation of the DLPFC with the use of transcranial direct current stimulation (tDCS) has found heterogenous results for motor learning tasks [7476]. A recent study using high-definition tDCS (HD-tDCS) to the DLPFC before the practice of an explicit MSL task found a decrease in performance after both anodal and cathodal HD-tDCS [74].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the DLPFC with the use of transcranial direct current stimulation (tDCS) has found heterogenous results for motor learning tasks [7476]. A recent study using high-definition tDCS (HD-tDCS) to the DLPFC before the practice of an explicit MSL task found a decrease in performance after both anodal and cathodal HD-tDCS [74]. Hashemirad and colleagues applied anodal tDCS to the DLPFC and the PPC separately during an MSL task.…”
Section: Discussionmentioning
confidence: 99%